Assessing a measurement instrument for studying student spin-off process development - Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez; Noor Azlinna, Azizan (Future Academy, 2018)
The establishment of student spin-off will provide many benefits such as economic development of the region where the university is located, commercialize knowledge and generate jobs to the community. However, the formation of student spin-off can be easily found in many developed countries. Hence, the student spin-off development in the context of higher education institutes should be further addressed in particular to developing countries in a way to increase the technology transfer to industry and reducing unemployment rate among graduates. This study aims to examine the reliability and validity of student spin-off process development instrument that covers three main stages which are pre-founding phase, founding and post-founding phase. Data for this study were collected from founders of student spin-off in Malaysian higher education institutes, and the measurement scales were tested on reliability. The results revealed that the instruments are valid and reliable. It is expected that this study will provide a useful measurement instrument to assess the process development of student spin-off for further research